Parametric Analysis of an Embankment Dam’s Stability - Bhutto, A. H.; Zardari, S.; Bhurgri, G. S.; Zardari, M. A.; Bhanbhro, R.; Babar, M. M.; Memon, B. A. (Engineering, Technology & Applied Science Research, 2019)
This paper presents a stability parametric analysis of a 59m high embankment dam. The analysis was performed in order to evaluate the minimum values of strength parameters that satisfy the stability requirements of the dam. The parametric analysis was conducted for three main zones of the dam: upstream shell, core, and downstream shell, which consisted of sandy gravel, clay, and random fill respectively. The friction angles of these materials were gradually decreased in order to represent different soil conditions. It was observed that stability requirements for the end of construction and after the filling of the reservoir could be satisfied if friction angle values of the sandy gravel and the random fill are 34º and 32º, instead of 37º and 34º. However, the value of the core’s cohesion could be utilized as 30º without any reduction so that the dam could be safe after the filling of the reservoir. The results of this study could be beneficial to practicing engineers for the design of safe and economical embankment dams.